Cooperative Team Learning and the Development of Social Skills in Higher Education: The Variables Involved - Mendo-Lázaro, Santiago; León-del-Barco, Benito; Felipe-Castaño, Elena; Polo-del-Río, María-Isabel; Iglesias-Gallego, Damián (Frontiers in Psychology, 2018)
The cooperative methodology provides an opportunity for university students to develop interpersonal, social and teamwork competences which can be decisive in their professional and social success. The research described here examines the influence of cooperative learning on the social skills necessary for teamwork. Furthermore, it analyses whether the continued use of this type of learning, the type of group, the basic social skills for teamwork, or the academic level of the students, influence their efficacy. To do so, we have designed a research project of a quasi-experimental kind with a pre-test, a post-test and a control group, in which 346 university undergraduate students studying degrees in Infant and Primary Education completed self-report surveys about behaviour patterns in social skills concerning self-assertion and the reception and imparting of information in teamwork situations. The results show that cooperative learning in university classrooms is effective as a method for developing the social skills necessary for teamwork, as well as the relevance of the control over the number of students in a group, the basic social skills, or the academic level of the students, as relevant factors related with efficacy; where continuity over time in the use of the cooperative methodology is what marks the greatest differences in the development of the social skills necessary for teamwork. It is important to stress that when students are asked to work autonomously in teams, with the aim of favouring the development of social skills, they should be given adequate structures that can guarantee the minimum conditions of participation, so as to allow a proper development of the said social skills.